2014
DOI: 10.1186/1742-4755-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal near miss and death among women with severe hypertensive disorders: a Brazilian multicenter surveillance study

Abstract: BackgroundHypertensive disorders represent the major cause of maternal morbidity in middle income countries. The main objective of this study was to identify the prevalence and factors associated with severe maternal outcomes in women with severe hypertensive disorders.MethodsThis was a cross-sectional, multicenter study, including 6706 women with severe hypertensive disorder from 27 maternity hospitals in Brazil. A prospective surveillance of severe maternal morbidity with data collected from medical charts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
4
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 49 publications
11
68
4
25
Order By: Relevance
“…The aspects that differ from the methodology of the study are shown in Table 2, along with each of the 13 articles. Cecatti et al 35 present overall results, and the other articles explore MNM according to age group 36 and with specific conditions: abortion, 37 ectopic pregnancy, 38 hypertensive diseases, 39,40 hemorrhage, 41,42 infections, 43,44 heart diseases. 45 Healthcare factors were also analyzed, such as quality of care 46 and the association with cesarean section 47 based on Robson's Classification.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aspects that differ from the methodology of the study are shown in Table 2, along with each of the 13 articles. Cecatti et al 35 present overall results, and the other articles explore MNM according to age group 36 and with specific conditions: abortion, 37 ectopic pregnancy, 38 hypertensive diseases, 39,40 hemorrhage, 41,42 infections, 43,44 heart diseases. 45 Healthcare factors were also analyzed, such as quality of care 46 and the association with cesarean section 47 based on Robson's Classification.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…They were organized in two research groups. The first refers to two articles from the "Nascer no Brasil" ("Born in Brazil") study, 5,34 the second reports 13 articles from the Multicenter Study of the "Rede Nacional de Vigilância de Morbidade Materna Grave" [35][36][37][38][39][40][41][42][43][44][45][46][47] ('National Surveillance Network on Severe Maternal Morbidity"). All articles of national scope used the WHO criteria for near miss.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…Dentre eles, pode-se destacar: gestação de alto risco; internações durante a gestação; comorbidades clínicas, principalmente hipertensão grave, infecções e hemorragias; partos cesáreos; uso de fórceps e necessidade de admissão em UTI (2,9,10,11) . Embora alguns estudos tenham associado maior ocorrência de Near Miss aos extremos da idade reprodutiva (2,9,12) , outros encontraram maior ocorrência dele em mulheres entre 20 e 35 anos (12,13,36) . Além da presença de comorbidades, a qualidade da atenção ao pré-natal e a presença de intercorrências que retardam o acesso ao serviço de saúde emergem como importantes fatores associados à MMG (17) .…”
Section: Discussionunclassified
“…Por apresentar uma maior proporção de casos com relação à ocorrência de óbitos (2) e por permitir que as próprias mulheres relatem o seu processo de adoecimento, a avaliação do Near Miss possibilita compreender os determinantes de morte em mulheres gravemente enfermas, possibilitando o desenvolvimento de estratégias efetivas para a redução da morbimortalidade materna, considerando que o desfecho é a única condição que as diferencia (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . Apesar disso, ainda existem poucos estudos sobre o impacto do Near Miss na vida dessas mulheres (5) .…”
Section: Introductionunclassified
“…Because of the sudden and rapid onset of PPH, earlier identification of risk factors may allow doctors to enact appropriate measures to reduce risk. Uterine inertia is the most common cause of PPH, accounting for 70%∼75% of reported cases [7][8][9][10][11]. This study analyzed, evaluated and predicted the risk of PPH from three perspectives: epidemiological, placental, and biochemical.…”
Section: Introductionmentioning
confidence: 99%